KEBERLANJUTAN ASUHAN KEBIDANAN PADA SITUASI BENCANA DAN DAMPAKNYA TERHADAP LUARAN KEGAWATDARURATAN IBU DAN BAYI - Elga Ceisaria Andani; Ainun Ganisia; Rakhmalia Imeldawati; Nurul Fathiyyah (Jurnal Medicare, 2024)
Background: Disasters can disrupt the continuity of maternal and infant healthcare services due to interrupted access to maternal and child health (MCH) books and referral systems. This situation may increase delays in recognizing danger signs and worsen maternal and neonatal emergency outcomes. Objective: This study aimed to analyze the continuity of midwifery care during disasters and its impact on maternal and infant emergency outcomes. Methods: This study used a descriptive-analytic design with a retrospective approach. Data were obtained through a post-disaster survey and simulation of a continuity of midwifery care model based on the integration of digital data and waterproof physical monitoring cards. The analysis assessed the relationship between care fragmentation and delays in recognizing danger signs, as well as the model's effectiveness in referral response time and the accuracy of complication detection. Results: As many as 42% of pregnant women lost access to their MCH books and medical records during evacuation. Care fragmentation was positively correlated with delays in recognizing danger signs among postpartum women (p < 0.05). The CoMC-Disaster model reduced referral response time by an average of 15 minutes and achieved 90% accuracy in early complication detection. In emergency deliveries, the model contributed to stabilizing neonatal outcomes, as indicated by a 5-minute Apgar score >7. Conclusion: The CoMC-Disaster model has the potential to strengthen the continuity of midwifery care and reduce delays in managing maternal and neonatal emergencies.